Distorted Norms: German Expressionist Prints and the Legacy of the Early German Masters - (:unkn) unknown (My University, 2019)
German Expressionism, one of the most influential art movements of the twentieth century, was the source of unprecedented experiments in printmaking. Although the works appear modern to our eyes, Expressionist printmakers drew heavily from the early history of printmaking, which emerged in northern Europe in the fifteenth and sixteenth centuries. The early history of the print included the development of the woodcut, the innovation of the printing press, and the invention of new printmaking techniques such as engraving and drypoint. The ways in which German Expressionists drew upon their heritage in printmaking is evident in three key ways: the revival of the woodcut, the distortion of the human figure, and social observation. Because German Expressionism embraced various styles and numerous artists, it has been challenging to clearly demonstrate how they looked back into the early German printmaking masters. However, the exhibition and catalogue for Distorted Norms: German Expressionist Prints and the Legacy of the Early German Masters reveals the visual connections between the two eras of printmaking and draws on two major strengths of UWM Art Collections.
Keywords: Distorted Norms; Early German Prints; Exhibition Catalogue; German Expressionism; German Expressionist Prints; Thesis Exhibition